The Impact of the Preparation Period on Endurance at Football Players U16 - Jovan Gardasevic; Dusko Bjelica; Marin Corluka (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The main aim of the research was to identify a level of quantitative changes of the endurance with U16 football players under the infl uence of the programmed football training of a six weeks preparation period. The training programme covered forty-four training units. The research was made on a sample of 120 football players U16. To estimate the endurance three tests have been used: Cooper test, Running 15 m long distance for 90 s, and Pin running persistence. In the area of comparative statistics, we used discriminant parametric procedure t-test for big paired samples. It can be concluded that there are statistically signifi cant diff erences in all three variables to estimate the endurance. This confi rmed the hypothesis that the expected signifi cant positive quantitative changes of endurance infl uenced by the proposed model of training in preparation period with football players U16. The authors were guided by the fact that this kind of training program in preparation period is very eff ective in terms of raising the endurance level with football players U16. The obtained results can be directed towards innovation plans and programs in the preparation period, and the adaptation of the same needs of the respective population.